Design and analysis of a rear wheel cover for a car using computational fluid dynamics (CFD) - Kogilan, Govindasamy (2009)
The performance and handling of automobile are significantly affected by its aerodynamic properties. One of the main causes of aerodynamic is about drag force and lifting force. This will influence all the aspect of the vehicles such as overall performance, fuel consumption, safety and stability. However, the unavoidable need for wheels caused and even recently causes significant problems for aerodynamicists to deal with the flow. The addition of wheelhouses and rotating wheels to an aerodynamically optimized car body, leads to decrease in drag and lift coefficients by 30% and 40%, respectively. In an aerodynamic field, the main important thing to get the stability, performance and good fuel consumption is to design a vehicle with low CD. The reduction of lift and flow separation is the key results that will be a point of discussion. Rear wheel cover will reduce the flow separation at the wheel houses that causing the turbulent airflow. The wake region also will be reduced and this will make the drag force that produce at the wheel houses will reduced. By the lower drag force will contribute to the lower fuel consumption. The task was done by doing a Computational Fluid Dynamic (CFD) analysis for expected vehicle speed of 40-140 km/h. A drag force was found based on inputs from CFD analysis. This force was calculated to produce the drag coefficient of the model as a whole. The approach needed to justify the amount of drag that can be reduced by addition of a rear wheel cover as compared to the model without the rear wheel cover. This project is to get an overall comparison of the velocity and pressure distribution before and after the rear wheel cover is added. The drag coefficient of the vehicle was decreases from 0.3882 to 0.3773 when adding the rear wheel cover.